Climatic and other responses to the Lakagígar 1783 and Tambora 1815 volcanic eruptions in the Czech Lands - Brázdil, Rudolf; Dolák, Lukáš; Kotyza, Oldřich; Valášek, Hubert; Řezníčková, Ladislava (2017)
Using documentary data and long-term temperature and precipitation series for the years 1775-2007, climatic, weather and other phenomena in the Czech Lands following the 1783 Lakagıgar eruption in Iceland and the 1815 Tambora eruption in Indonesia are investigated. The Lakagıgar eruption had clear post-volcanic effects on the weather in central Europe (dry fog, heavy thunderstorms, optical phenomena), with the occurrence of significant cold temperature anomalies in winter 1783/84, spring 1785 and the summer and autumn of 1786. The Tambora eruption was not accompanied by any particular weather phenomena, but was followed by an extremely cold summer in 1816. A comparison of the two eruptions shows that the effects of the Lakagıgar eruption were climatologically stronger than those of the Tambora eruption. 147 168